Using Performance Indicators for Hospital Quality Management: A Qualitative Interview Study amongst Health Professionals and Quality Managers in the Netherlands - Botje, Daan; Asbroek, Guus ten; Plochg, Thomas; Anema, Helen; Kringos, Dionne S.; Fischer, Claudia; Wagner, Cordula; Klazinga, Niek S. (Current Overview on Disease and Health Research Vol. 3, 2022)
The aim of this study was to explore hospitals’ use of performance indicators for internal quality management activities. The study conducted a qualitative interview among 72 health professionals and quality managers in 14 acute care hospitals in The Netherlands. The goal was to gain insight into data collection and use of performance indicators for two conditions: knee and hip replacement surgery and breast cancer surgery. Based on the data, themes were synthesized and the analyses were executed systematically by two analysts independently. Hospitals collect data for performance indicators and use it for quality management in different ways, while some do not seem to use the data for this purpose at all. Factors like ‘linking pin champions’, pro-active quality managers and engaged medical specialists seem to make a difference. A comprehensive hospital data infrastructure with electronic patient records and robust data collection software appears to be a prerequisite to produce reliable performance data for internal quality improvement. Performance indicators are frequently used by hospitals as a tool to help internal quality control. It is advised that hospitals concentrate their human resource policies on "connecting pin champions," the employment of experts and a proactive quality manager, and to make investments in a robust data infrastructure. Furthermore, it is challenging to compare the results of performance metrics among Dutch hospitals due to variations in data collection procedures.